Effect off ollicular fluid proteins on post-thaw characteristics of buffalo spermatozoa - KUMARESAN, A; GARG, ABHISHEK; SURESH, V; ANSARI, M R (The Indian Journal of Animal Reproduction, 2023)
Follicular fluid collected from buffalo ovaries obtained from slaughter house was exposed to SDS-PAGE to study the electrophoretic profiles of follicular proteins (FP). A total number of 28 protein bands were obseived, of which, I 0, I 4 and 4 were of >97, 29-97 and <29 kDa, respectively. No follicular fluid specific protein could be observed. Follicular proteins isolated by ammonium sulphate precipitation and dialysis were added to frozen thawed buffalo semen at the rate of I, 2, 4, 8 and 16 mg/ml and incubated for 4 h at 37°C. Samples were evaluated for motility, viability and acrosomal integrity measurements immediately after thawing and at hourly inteival. A net beneficial effect of FP on spermatozoan motility, viability and acrosomal integrity was obseived in samples added with I mg/ml of FP. Samples containing higher FP (>4 mg/ml) showed inferior spermatozoan characteristics than that of control. From this study it is inferred that FP have a beneficial effect on spermatozoan function in a dose dependent pattern.